Assessing the Impact of Price Promotions on Consumer Response to Online Stockouts. Issue 3 (12th August 2015) - Peinkofer, Simone T.; Esper, Terry L.; Smith, Ronn J.; Williams, Brent D.
Abstract : The recent growth of e‐commerce technologies has disrupted the traditional retail environment, leading to more consumers shopping online. While the manner in which consumers shop is changing rapidly, our understanding of how changing consumer behaviors affect retail supply chain management is lacking. In particular, our understanding of how consumers react to stockouts in an online shopping environment remains unclear. Making the challenge even more difficult is the fact that price promotions are heavily used to attract consumers in an online retail environment where consumer switching costs are low. This research develops a theoretical framework, based on expectation‐disconfirmation theory, to explain the effect of price promotions on consumer expectations of product availability and their reactions to stockouts in an online retail environment. Surprisingly, our findings suggest that consumers are actually less dissatisfied with a stockout of a price promoted item than a nonprice promoted product and are less likely to switch to another retailer's website. These findings may suggest that price promotions actually create a type of switching cost in the online retail environment, leading to interesting implications for researchers and supply chain managers.